PENAMBAHAN LATIHAN CORE STABILITY PADA PROGRAM PELATIHAN ATLET DAYUNG UNTUK PENINGKATAN KECEPATAN MENDAYUNG - Christanto, Dyno Aryo; Adiputra, N.; Lesmana, S. Indra; Sutjana, Dw P.; Muliarta, Made; -, Wahyuddin (Sport and Fitness Journal; Volume 5, No.3, 2017DO - 10.24843/spj.2017.v05.i03.p06, 2017)
Introduction: Generally, core stability exercise as a training program is needed in almost kind of sport including paddle, analysis of movement in any kind of paddle sport such as kayak, canoe, or even rowing have been showed that the activity of core stability muscles are really needed. Purpose: purpose of this research is to know the effectivity of core stability exercise replenishment to increase sculling speed in paddle training program. Methods: This research is experimental with treatment by subject design project, involving 15 paddle athletes which divided into two groups and consists of II periods which are, Period I and Period II. In the 1st period, the athletes were given extra core stability exercise along with their normal paddling routine mean while in the 2nd period, the athletes only doing their normal paddling routine. Each period do the trial in 6 weeks, so this reseach took 12 weeks. In 1st period, the subjects were given extra core stability training 3 times a week along with their normal paddling routine where as subjects in period II only do their normal paddling routine. Results: The used of parametric paired t test is to know the difference of sculling speed before and after the trials were given. To period I pre test value is 3.80 ± 0.26 meters/second while the post test value is 4.06 ± 0.41 meters/second and the value 0.001 (p<0.05)mean while the 2nd period use Wilcoxon signed rank test to know the difference of sculling speed between before and after the trial were given resulting pre test value 3.80 ± 0.22 meters/second and post test value 3.91 ± 0.27 meters/second while the p value is 0.004 (p<0.05). After 12 weeks of sculling speed test between both period using Wilcoxon signed rank test and resulting obvions with period I value 0.26 ± 0.20 meters/second and period II value is 0.11 ± 0.12 meters/second along with p value 0.001 (p<0.05). Conclusion: Therefore, based on the result of my research test, we can concluded that the addition of core stability exercise in paddle training program is more effective to increase sculling speed.